EMU and European capital markets : towards a unified financial market - Gamble, Andrew (1991)
Informe de Delors. Ecu fuerte. Otras iniciativas comunitarias. Mercado de capitales
Keywords: Comunidad Europea; Mercado financiero; Mercado de la UE